2007
DOI: 10.1007/s00018-007-7198-4
|View full text |Cite
|
Sign up to set email alerts
|

The family of iron responsive RNA structures regulated by changes in cellular iron and oxygen

Abstract: The life of aerobes is dependent on iron and oxygen for efficient bioenergetics. Due to potential risks associated with iron/oxygen chemistry, iron acquisition, concentration, storage, utilization, and efflux are tightly regulated in the cell. A central role in regulating iron/oxygen chemistry in animals is played by mRNA translation or turnover via the iron responsive element (IRE)/iron regulatory protein (IRP) system. The IRE family is composed of three-dimensional RNA structures located in 3' or 5' untransl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 124 publications
3
82
0
2
Order By: Relevance
“…Another important feature of IREB2 is that it is suggested to be active at lower oxygen tensions 23 and has been observed to be post-translationally regulated by hypoxia. 24,25 Thus, the aberrant iron homeostasis in the presence of hypoxia could lead to increased oxidative stress resulting in tissue damage and reduced FEV 1 . Functional studies will be required to clarify the role of iron regulation in COPD pathogenesis in the future.…”
Section: Association Of Ireb2 and Chrna3/5 With Copd In A Chinese Hanmentioning
confidence: 99%
“…Another important feature of IREB2 is that it is suggested to be active at lower oxygen tensions 23 and has been observed to be post-translationally regulated by hypoxia. 24,25 Thus, the aberrant iron homeostasis in the presence of hypoxia could lead to increased oxidative stress resulting in tissue damage and reduced FEV 1 . Functional studies will be required to clarify the role of iron regulation in COPD pathogenesis in the future.…”
Section: Association Of Ireb2 and Chrna3/5 With Copd In A Chinese Hanmentioning
confidence: 99%
“…Iron regulatory proteins (IRPs) function as critical components of a sensory and regulatory network that controls cellular iron homeostasis in vertebrates (Wallander et al 2006; Leipuviene and Theil 2007;Muckenthaler et al 2008). IRPs bind iron-responsive elements (IREs) in the untranslated region of mRNA encoding proteins involved in iron metabolism, or in the adaptive response to changes in iron availability, and regulate their translation or stability.…”
Section: Introductionmentioning
confidence: 99%
“…To date six mammalian mRNAs encoding proteins of widely different function have been identified that possess 59 IREs. These mRNAs encode the erythroid-specific isoform of 5-aminolevulinate synthase (eALAS), which catalyzes the first step in heme synthesis; the H and L subunits of the iron storage protein ferritin; the iron exporter ferroportin; mitochondrial aconitase (m-acon), which is the second enzyme of the tricarboxylic acid cycle; and the hypoxia-inducible transcription factor HIF 2a (also known as EPAS1) (Wallander et al 2006;Leipuviene and Theil 2007;Muckenthaler et al 2008). Given the varied function of proteins encoded by mRNA containing 59 IREs, it seems likely that IRPs differentially control translation of these mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Stewart G. Stevens, 1 Paul P. Gardner 2 and Chris M. Brown 1, tri-loop (A15, G16, U17) and that two bases (a C8 and U6) are bulged from the hairpin stem. These structures 9,10 did confirm the predicted secondary structure of an A-form helical stem, interrupted by a mid-stem C8 bulge, with an apical loop that presents conserved bases interacting with IRE binding proteins.…”
Section: Two Covariance Models For Iron-responsive Elementsmentioning
confidence: 99%
“…1 Since then, IREs have been found in both the 5' and 3' UTRs of diverse mRNAs over a wide phylogenetic range-mainly eukaryotic animals and also some prokaryotes, but not plants. 2 Iron regulatory proteins 1 and 2 (IRP1 and IRP2) bind to IREs in low iron conditions. In high iron conditions IRP1 binds to iron complexes, adopting conformations unsuitable for IRE binding.…”
Section: Introductionmentioning
confidence: 99%